2007
DOI: 10.1080/08916930601167343
|View full text |Cite
|
Sign up to set email alerts
|

Green tea polyphenols reduce autoimmune symptoms in a murine model for human Sjogren's syndrome and protect human salivary acinar cells from TNF-α-induced cytotoxicity

Abstract: Sjogren's syndrome (SS) is a relatively common autoimmune disorder. A key feature of SS is lymphocytic infiltration of the salivary and lacrimal glands, associated with the destruction of secretory functions of these glands. Current treatment of SS targets the symptoms but is unable to reduce or prevent the damage to the glands. We reported previously that the major green tea polyphenol (GTP) epigallocatechin-3-gallate (EGCG) inhibits autoantigen expression in normal human keratinocytes and immortalized normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 38 publications
1
51
1
1
Order By: Relevance
“…Most evidence suggesting an anti-inflammation property of EGCG is from cell-based studies in which EGCG is added at much higher than physiologically relevant concentrations. A few studies in animal studies using oral administration of EGCG or green tea polyphenols have been reported on some autoimmune diseases, such as rheumatoid arthritis, 19 Sjögren's syndrome, 40 colitis, 41 and encephalomyelitis. 17 These studies have shown, to a varied extent, EGCG's ability to improve symptoms, pathological characteristics, and the cytokine profile.…”
Section: Discussionmentioning
confidence: 99%
“…Most evidence suggesting an anti-inflammation property of EGCG is from cell-based studies in which EGCG is added at much higher than physiologically relevant concentrations. A few studies in animal studies using oral administration of EGCG or green tea polyphenols have been reported on some autoimmune diseases, such as rheumatoid arthritis, 19 Sjögren's syndrome, 40 colitis, 41 and encephalomyelitis. 17 These studies have shown, to a varied extent, EGCG's ability to improve symptoms, pathological characteristics, and the cytokine profile.…”
Section: Discussionmentioning
confidence: 99%
“…EGCG has recently attracted attention for its emerging antiarthritic and immunemodulating properties (15)(16)(17). Our previous studies on EGCG defined the mechanisms of its inhibitory potential against the mediators of inflammation and cartilage degradation in human chondrocytes (16,18,19).…”
mentioning
confidence: 99%
“…In this investigation, to imitate the clinical scenario of RA, CIA was induced in Lewis rats and subsequently, the anti-arthritic potency of Camellia sinensis stew was assessed in mentioned experimental model. This beverage is being used for many years and possesses antioxidant activities, anti-inflammatory, anti-apoptotic properties and protective effects in autoimmune animal models [11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%